HHIP’s dynamic role in epithelial wound healing reveals a potential mechanism of COPD susceptibility - Dávid Deritei; Wardatul Jannat Anamika; Anny Xiaobo Zhou; Jeong H. Yun; Maor Sauler; Michael H. Cho; Edwin K. Silverman; Erzsébet Ravasz Regan; Kimberly Glass (Proceedings of the National Academy of Sciences, 2026)
Genetic variants near Hedgehog interacting protein ( HHIP ) have been consistently associated with increased risk for chronic obstructive pulmonary disease (COPD), the third leading cause of death worldwide. However, HHIP ’s role in COPD pathogenesis remains elusive. Canonically, HHIP is a negative regulator of the Hedgehog pathway and downstream GLI1 and GLI2 activation. The Hedgehog pathway plays an important role in wound healing, specifically in activating transcription factors that drive the epithelial–mesenchymal transition (EMT), which in its intermediate state (partial EMT) is necessary for the collective movement of cells closing a wound. Herein, we use a systems biology approach to propose a mechanism to explain HHIP’s role in faulty epithelial wound healing, which could contribute to the development of emphysema, a key feature of COPD. Using two different Boolean models, we show dysfunctional HHIP results in a lack of negative feedback on GLI, triggering a full EMT, where cells become mesenchymal and do not properly close the wound. We validate these Boolean models with experimental evidence gathered from published scientific literature. Finally, we show evidence supporting our hypothesis in single-cell and single-nucleus RNA-Seq data from different COPD cohorts and Hhip heterozygous knockout mice. Overall, our analyses suggest that aberrant wound healing due to dysfunctional HHIP, combined with chronic epithelial damage through cigarette smoke exposure, may be a primary cause of COPD-associated emphysema.